Neurotic needs of Light Yagami in the anime series Death Note - Pangestu, Anggoro Margi; Saifudin, Akhmad (Japanese Research on Linguistics, Literature, and Culture, 2025)
This study investigates the psychological dynamics of Light Yagami, the protagonist of the anime Death Note, through the lens of Horney’s theory. Employing a qualitative descriptive design, the research analyzes selected scenes, dialogues, and behavioral patterns that reflect underlying neurotic tendencies. Data were drawn from the anime consisting of 37 episodes, from which 11 representative scenes were purposively selected based on their relevance to Horney’s theoretical categories. Qualitative content analysis was applied to link narrative elements with six dominant neurotic needs systematically. The results reveal that Light Yagami exhibits a coherent constellation of neurotic needs, including affection and approval, power, exploitation, personal achievement, social recognition, and perfection or unassailability. These needs emerge dynamically across the narrative, with an observable shift from early compliant tendencies toward aggressive neurotic trends following Light’s acquisition of the Death Note. The neurotic need for power functions as the central compensatory mechanism, while exploitation, achievement, and recognition reinforce an idealized self-image characterized by superiority and moral absolutism. Perfectionism operates as an integrative yet destabilizing force, ultimately contributing to psychological rigidity and self-defeat. The study concludes that Light’s transformation is best understood not merely as a moral or ideological descent but as the escalation of anxiety-driven neurotic defenses enabled by extraordinary external power. By applying Horney’s framework, this research demonstrates the analytical value of neo-Freudian personality theory for character studies and media psychology, particularly in interpreting morally ambiguous characters. The findings contribute to interdisciplinary approaches that integrate psychological theory, qualitative narrative analysis, and media-based personality construction.